PERSEPSI GURU TERHADAP PENGGUNAAN CANVA SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA - Mulya, Nana (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
The development of technology in the 21st century, has an impact on the development of the world of Education. Technology is one of the media to obtain knowledge that should be welcomed by teachers and used as an encouragement to adopt technology for the benefit of learning. . Teachers are required to be facilitators in learning and are expected to be able to understand the use and utilization of tools and applications to facilitate the preparation and teaching and learning process, so teachers are also required to be able to create learning media by utilizing technology. Canva is one application that can be used by teachers to create practical and innovative learning media. This article focuses on investigating teachers' perceptions of using Canva as a medium for learning mathematics. The participants of the study were 30 mathematics teachers in North Aceh. Data were collected through questionnaire and interview. Data were analyzed by tabulating data. The result revealed that most of the teachers (76%) are agreed that Canva easier for teachers to design more creative and innovative learning media. The use of Canva as a learning medium is very practical and very helpful in increasing student understanding. Teachers feel an increase such as, students who are more focused when learning, the classroom atmosphere becomes more orderly and conducive.